2015
DOI: 10.1089/cap.2015.29000.bjc
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome in a Boy with NMDA Receptor Encephalitis

Abstract: Chief Complaint and Presenting ProblemM . is an 11-year-old African American boy who was referred to the psychiatry consult liaison service eight days after admission to an epilepsy monitoring unit for behavioral disruption and inability to sleep. History of Present IllnessParents reported that M. had been a normally developing fifth grader who did well in school. M. developed the sudden onset of seizures six weeks prior to admission; his family found him curled in a fetal position with irregular jerking movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The search identified 862 potentially relevant studies, and 201 were selected for data extraction. From these, 48 references met inclusion criteria, including 27 individual case reports and 21 case series (Figure 1 ) ( 4 , 10 12 , 14 , 15 , 17 57 ). Two prospective cohort studies were found ( 45 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…The search identified 862 potentially relevant studies, and 201 were selected for data extraction. From these, 48 references met inclusion criteria, including 27 individual case reports and 21 case series (Figure 1 ) ( 4 , 10 12 , 14 , 15 , 17 57 ). Two prospective cohort studies were found ( 45 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…36 Another potential diagnostic challenge for clinicians managing these patients is the degree to which clinical features of anti-NMDArE and neuroleptic malignant syndrome (NMS) can overlap. There are many case reports [37][38][39][40][41][42] in which a diagnosis or strong suspicion of NMS delayed recognition of anti-NMDArE, which can be attributed to the fact that these patients are often severely ill and present with behavioral symptoms for which antipsychotic medications would ordinarily be prescribed. In a series of 45 anti-NMDArE adults erroneously admitted to a psychiatric unit, the suspicion of NMS was so high that 21 patients (46.6%) were subsequently transferred to a medical service.…”
Section: Discussionmentioning
confidence: 99%
“…Besides PERM, there have also been increasing reports of other immune-mediated encephalitis presenting with an NMS phenotype, including anti-NMDAR [3,4] and anti-VGKCC [5] encephalitis. These frequently present with neuropsychiatric manifestations.…”
Section: Discussionmentioning
confidence: 99%